Good Corporate Governance, Corporate Social Responsibility dan Konservatisme Akuntansi: Agresivitas Pajak - Novita Salsabela; Sri Andriani (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2023)
Purpose: This research was conducted to obtain empirical evidence regarding the relationship between the proportion of independent commissioners, audit committees, audit quality, corporate social responsibility and accounting conservatism on tax aggressiveness.Method: This study uses a descriptive quantitative approach. Secondary data is data used in research, where the data was obtained from the LQ45 company database that was registered on the IDX for a period of five years, namely from 2017-2021. During this time interval, 16 LQ45 indexed companies were selected as research samples using purposive sampling method. Multiple linear regression analysis with the help of SPSS version 26 is the method of data analysis in research.Results: The results of the study prove that partially the proportion of independent commissioners, audit committees, corporate social responsibility, and accounting conservatism has no significant effect on tax aggressiveness. Meanwhile, audit quality partially has a significant effect on tax aggressiveness. The proportion of independent commissioners, audit committees, audit quality, corporate social responsibility, and accounting conservatism simultaneously have a significant effect on tax aggressiveness.Implications: This research can be used as material for evaluation and review for the government in relation to the established tax policies. In addition, it is hoped that it will further increase company awareness and compliance with regard to fulfilling its tax obligations as well as material for consideration in the application of corporate governance policies.Novelty: The majority of previous research examined manufacturing companies, while this study chose to examine research variables with the perspective of different research objects, namely LQ45 indexed companies.